Drilling response of impregnated diamond bits: modelling and experimental investigations - Mostofi, Masood (Curtin University, 2014)
The research aims to develop bit/rock interaction models for Impregnated Diamond (ID) bits. An experimental approach is used to study the dominant cutting and wear processes governing the bit/rock interface. The developed models are used to investigate the effects of the bit and rock properties as well as operating conditions on the drilling response. Furthermore, a field case study is performed, at which the drilling data is analysed using the framework of the model.